Diagnostic Utility of Radiomics in Thyroid and Head and Neck Cancers - Gul, Maryam; Bonjoc, Kimberley-Jane C.; Gorlin, David; Wong, Chi Wah; Salem, Amirah; La, Vincent; Filippov, Aleksandr; Chaudhry, Abbas; Imam, Muhammad H.; Chaudhry, Ammar A. (Frontiers in Oncology, 2021)
Radiomics is an emerging field in radiology that utilizes advanced statistical data characterizing algorithms to evaluate medical imaging and objectively quantify characteristics of a given disease. Due to morphologic heterogeneity and genetic variation intrinsic to neoplasms, radiomics have the potential to provide a unique insight into the underlying tumor and tumor microenvironment. Radiomics has been gaining popularity due to potential applications in disease quantification, predictive modeling, treatment planning, and response assessment – paving way for the advancement of personalized medicine. However, producing a reliable radiomic model requires careful evaluation and construction to be translated into clinical practices that have varying software and/or medical equipment. We aim to review the diagnostic utility of radiomics in otorhinolaryngology, including both cancers of the head and neck as well as the thyroid.